2018
DOI: 10.1016/j.culher.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Geological risk assessment for rock art protection in karstic caves (Alkerdi Caves, Navarre, Spain)

Abstract: This paper sets out a methodology for calculating the potential zone of damage to which an Item of Cultural Interest (ICI) located in a karst environment is exposed. An itemised study of the geological characteristics of the cave environment is proposed: lithological cartography, endokarst and exokarst geomorphology and the study of fracturing of the limestone massif. Based on these data and using a Geographical Information System (GIS), it was possible to calculate the degree of the geological threats on a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…); environmental (water interaction and weathering); biological (biomass growth); and anthropic (human presence, site planning, local urbanization and exploitation of natural resources) [3]. The risk can be quantified and mapped with the support of geographic information systems and numerical modelling [4,5]. Anthropic factors are often the most critical, and indirectly increase the environmental and biological risks.…”
Section: Caves In Heritage Sciencementioning
confidence: 99%
“…); environmental (water interaction and weathering); biological (biomass growth); and anthropic (human presence, site planning, local urbanization and exploitation of natural resources) [3]. The risk can be quantified and mapped with the support of geographic information systems and numerical modelling [4,5]. Anthropic factors are often the most critical, and indirectly increase the environmental and biological risks.…”
Section: Caves In Heritage Sciencementioning
confidence: 99%
“…In the case of archaeological valuable sites that need to be protected, such as a Palaeolithic rock art paintings and engravings, the fragility of this natural system requires us to be more responsible and the control any activity that would produce irreversible alteration processes [3,5,[8][9][10][11]. Mining has been identified as an activity capable of inducing enough changes to a natural karstic system that can modify the original conditions of the system, such as collapses, removal or alteration of the soil cover, changes in the water infiltration rate, and in its chemical composition [7,[12][13][14][15][16][17][18]. At the Spanish and French Round Table on the Protection and Conservation of Palaeolithic Rock Art, which took place in Colombres (Asturias, Spain) in 1991, it was concluded that, in case of rock-art painting in caves, the comprehension of the balance between karstic and environmental parameters is a key factor in the conservation of the rock-art heritage [19,20].…”
Section: Introductionmentioning
confidence: 99%